BUILDING HEALTH BRIDGES FOR BPJS PATIENTS BY STRENGTHENING THE LINK OF PREMIUM COSTS, INFRASTRUCTURE, SERVICE QUALITY, EMPLOYEE PERFORMANCE, AND PATIENT SATISFACTION - Sarida Minarni; Meiliyah Ariani; Melan Susanty Purnamasari (ZILLZELL MEDIA PRIMA, 2024)
Health is one of the most important parts of human rights (HAM), Everyone has the right to an adequate standard of living for the health and well-being of himself and his family as mentioned in the United Nations (UN) Declaration of the Right of Human Rights on November 10, 1948. Public services are an important indicator in assessing government performance, both at the central and regional levels. The quality of public services is a dynamic condition related to products, services, processes and the environment, the quality assessment is determined at the time of the provision of public services. The administration of government is said to be good if the public services carried out are oriented to the interests of realizing the welfare of the community. This study aims to explain the relationship between premium costs, infrastructure, service quality, and employee performance on patient satisfaction of BPJS Kesehatan health facility level three users at dr. Chasbullah Abdulmadjid Hospital, Bekasi City. This study uses a quantitative approach. The data used is primary data. The object of the research used is the Bekasi City Regional General Hospital. The method used for sampling was accidental sampling of 126 respondents. This study was tested using the SEM-PLS (Structural Equation Model-Partial Least Square) system and the data was tested using SmartPLS software. The results of the study showed that the variables of premium costs and infrastructure did not have a significant effect on patient satisfaction of BPJS Kesehatan users, while the variables of service quality and employee performance had a significant effect on BPJS Kesehatan patient satisfaction.